The Risk of Second Primary Cancers in Prostate Cancer Survivors Treated in the Modern Radiotherapy Era - Jahreiß, Marie-Christina; Aben, Katja K. H.; Hoogeman, Mischa S.; Dirkx, Maarten L. P.; de Vries, Kim C.; Incrocci, Luca; Heemsbergen, Wilma D. (Frontiers in Oncology, 2020)
Purpose: Concerns have been raised that modern intensity modulated radiotherapy (IMRT) may be associated with increased second primary cancer risks (SPC) compared to previous three-dimensional conformal radiation techniques (3DCRT), due to increased low dose volumes and more out-of-field ionizing dose to peripheral tissue further away from the target. We assessed the impact of treatment technique on SPC risks in a cohort of prostate cancer (PCa) survivors. Material and Methods: The study cohort comprised 1,561 PCa survivors aged 50-79 years at time of radiotherapy, treated between 2006-2013 (N=707 IMRT, N=854 3DCRT). Treatment details were extracted from radiotherapy systems and merged with longitudinal data of the Netherlands Cancer Registry to identify SPCs. Primary endpoint was the development of a solid SPC (excluding skin cancer) in peripheral anatomical regions, i.e. non-pelvic. Applied latency period was 12 months. SPC rates in the IMRT cohort (total cohort and age subgroups) were compared to 1) the 3DCRT cohort by calculating Sub-Hazard Ratios (sHR) using a competing risk model, and 2) to the general male population by calculating Standardized Incidence Ratios (SIR). Models were adjusted for calendar period and age. Results: Median follow-up was 8.0 years (accumulated 11,664 person-years at-risk) with 159 cases developing ≥1 non-pelvic SPC. For IMRT vs 3DCRT we observed a significantly (p=0.03) increased risk (sHR=1.56, 95% Confidence Interval (CI) 1.03-2.36) with an excess absolute risk of +7 cases per 10,000 person-years. At explorative analysis, IMRT was in particular associated with increased risks within the subgroup of active smokers (sHR 2.94, p=0.01). Within the age subgroups 50-69 and 70-79 years, the sHR for non-pelvic SPC was 3.27 (p=0.001) and 0.96 (p=0.9), respectively. For pelvic SPC no increase was observed (sHR=0.8, p=0.4). Compared to the general population, IMRT was associated with significantly increased risks for non-pelvic SPC in the 50-69 year age group (SIR=1.90, p<0.05) but not in the 70-79 years group (SIR=1.08). Conclusion: IMRT is associated with increased SPC risks for subjects who are relatively young at time of treatment. Additional research on aspects of IMRT that may cause this effect is essential to minimize risks for future patients receiving modern radiotherapy.